A Comparison of the Effects of Foam Rolling and Stretching on Physical Performance. A Systematic Review and Meta-Analysis - Konrad, Andreas; Tilp, Markus; Nakamura, Masatoshi (Frontiers in Physiology, 2021)
Foam rolling and stretching with its various techniques are frequently used as a warm-up routine to increase the range of motion of a joint. While the magnitude of the changes in range of motion between foam rolling and stretching (static and dynamic technique) is similar, it is not clear if this also holds true for performance parameters (e.g. strength, jump height). The purpose of this meta-analysis was to compare the effects of an acute bout of foam rolling (with and without vibration) with the effects of an acute bout of stretching (with all techniques included) on performance parameters in healthy participants. We assessed the results from 13 studies and 35 effect sizes by applying a random-effect meta-analysis. Moreover, by applying a mixed-effect model, we performed subgroup analyses with the stretching technique, type of foam rolling, tested muscle, treatment duration, and type of task. We found no significant overall effect, and the analysis revealed only a trend of the performance parameters in favor of foam rolling when compared to stretching (when considering all techniques). Significantly favorable effects of foam rolling on performance were detected with subgroup analyses when compared to static stretching, when applied to some muscles (e.g. quadriceps) or some tasks (e.g. strength), when applied for longer than 60 s, or when the foam rolling included vibration. When foam rolling was compared to dynamic stretching or applied in the non-vibration mode, the same magnitude of effect was observed. While the present meta-analysis revealed no significantly different effect between foam rolling and stretching (including all techniques) prior to exercise, differences could be observed under specific conditions (e.g. when compared to static stretching).